GERAKAN EDUKASI DALAM PENCEGAHAN STUNTING DAN PERILAKU ODF PADA MASYARAKAT DESA JAYALAKSANA - Juniati, Ainun; Akmalsyah Rahman, Rafi; Marlina, Selly; Sopandi, Andi; Irham, Irham (Universitas Islam 45 Bekasi, 2023)
A clean environment is very important because it has a big impact on children's health and growth. Children's growth can also be disrupted due to a polluted environment. ODF behavior can be a factor in stunting in an area. Open Defecation Free (ODF) in Indonesia is still a problem, 33 out of 34 provinces in Indonesia are still not 100% verified as ODF, in Bekasi district itself there are still many areas that carry out ODF behavior and the reduction in stunting cases has not yet reached the target.This community service uses counseling and training methods.The aim of this research is to achieve